Numerical heat transfer in a solar air heater duct with punched delta-winglet vortex generators - Pongjet Promvonge; Pitak Promthaisong; Sompol Skullong (My University, 2021)
The flow topology and thermohydraulic performance of a novel designed punched delta-winglet (P-DW) placed on the absorber of a solar air heater duct are numerically explored. The effects of geometrical parameters, namely, the relative winglet pitch, PR = 1–2 and the relative punched hole size, dR = 0–0.583 at a single value of blockage ratio, BR = 0.48 and attack angle, α = 30° on thermal characteristics are proposed for Reynolds number from 4000 to 24,000. Among several turbulence models, the simulation has shown that the realizable k–ε turbulence model is favorable with respect to measurements. For flow patterns, the P-DW produces several counter-spinning vortices helping induce the impinging jets onto the absorber surface whilst for thermal behaviors, the decline of PR and dR leads to the rise in the friction factor (f) and Nusselt number (Nu). The P-DW provides greater Nu and f than the plain flat plate by 17.1–78.21 and 3.92–5.9 times, respectively and gives the highest performance around 2.1. Further, the P-DW is modified by covering the punched hole partially with a circular flap, called the flapped delta-winglet (F-DW) and this F-DW yields the greatest performance around 2.16 higher than the P-DW about 2.9%.
Keywords: Wingtip device; Vortex generator; Heat Transfer Mechanisms